PENGENALAN PERBANKAN SYARIAH MELALUI BIMBINGAN BELAJAR MURID SEKOLAH DASAR DAN SEKOLAH MENENGAH PERTAMA DI KAMPUNG CIBEUREUM, DESA CIBATOK II, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Fitri Ali Rahmayani; Tubagus Rifqy Thantawi; Miftakhul Anwar (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract Teaching and learning activities are usually carried out face to face between teachers and students in schools. However, due to the ongoing Covid-19 pandemic, learning activities are hampered, so teaching and learning activities are carried out online. Not a few who complain about this phenomenon. Various difficulties were encountered including the limitations of parents or guardians of students delivering learning materials at home, the availability of facilities and infrastructure owned and the ability of students to receive subject matter. Things like that can hinder learning activities. Tutoring is provided as a form of assistance for students and parents to solve the difficulties encountered during the online learning process. However, this needs to be harmonized with the introduction of Islamic Banking so that learning activities can continue, but the introduction of Islamic Banking can still be carried out. The tutoring as well as an introduction to Islamic Banking was given to Elementary School (SD) and Junior High School (SMP) students in Cibeureum Village, Cibatok II Village, Cibungbulang District, Bogor Regency. Students simply understand the subject matter provided through this tutoring as well as get to know Islamic Banking from an early age. Keywords: Covid-19, Tutoring, Introduction to Islamic Banking.